A longitudinal assessment of appetite loss and nutritional care among postoperative patients in Vietnam - Nguyen, Tu Huu; Ta, Nguyet Thi; Dang, Anh Kim; Nguyen, Tham Thi; Dam, Vu Anh Trong; Latkin, Carl A.; Ho, Cyrus S. H.; Ho, Roger C. M. (Frontiers in Nutrition, 2023)
Background: Post-operative appetite loss is an important complication affecting surgical outcomes. It has been estimated that nearly 60% of patients having gastrointestinal or major elective surgeries suffer from malnutrition. Appetite refers to the physical desire for food appetite, and losing appetite after surgery may result in a decrease in body weight, impairment of intestinal absorption and eventually, malnutrition among postoperative patients. This study aims to assess appetite status and other relevant factors among abdominal postoperative patients in Vietnam. Methods: A cross-sectional study was conducted on 169 abdominal postoperative patients from June 1st to August 30th, 2016 at Hanoi Medical University Hospital, Hanoi, Vietnam. Appetite score was computed by using the Council on Nutrition Appetite Questionnaire (CNAQ). This study used GEE to account for the potential correlation of outcomes of the longitudinal assessment, assuming an independent correlation structure. Results: The primary and secondary outcome measures: highest average appetite score was recorded in the preoperative day and the score declined throughout seven-day duration. Patients who were female, under general anesthetics and being under open surgery tended to get lower appetite scores. The majority of patients had moderate to good appetite in both the preoperative day and seven days post-operation. Conclusion: Women should receive more care and help in regaining their appetite after surgery. Treatment for appetite loss through non-pharmaceutical measures should be prioritized. Interventions that increase the appetite of patients after abdominal surgery should be targeted on patients being under general anesthetic as well as open surgery and be undertaken with caution